Prevalence, Awareness, and Control of Arterial Hypertension in a Russian Population. The Ural Eye and Medical Study - Bikbov, Mukharram M.; Kazakbaeva, Gyulli M.; Zainullin, Rinat M.; Salavatova, Venera F.; Gilmanshin, Timur R.; Yakupova, Dilya F.; Uzianbaeva, Yulia V.; Arslangareeva, Inga I.; Panda-Jonas, Songhomitra; Mukhamadieva, Svetlana R.; Khikmatullin, Renat I.; Aminev, Said K.; et al. (Frontiers in Public Health, 2020)
Background: Applying the criteria recently published by the American College of Cardiology/American Heart Association for the definition of arterial hypertension, we investigated prevalence and awareness of arterial hypertension in Russia. This new definition differentiates between normal BP [SBP (systolic blood pressure)/DBP (diastolic blood pressure) < 120/80 mmHg], elevated BP (SBP 120–129 mmHg; DBP < 80 mmHg), hypertension stage 1 (SBP 130–139 mmHg or DBP 80–89 mmHg), hypertension stage 2 (SBP ≥ 140 and ≤180 mmHg or DBP ≥ 90 and ≤120 mm Hg) and hypertensive crisis (SBP > 180 mmHg and/or DBP > 120). Methods: The population-based Ural Eye and Medical Study, performed in an urban and rural region in the Russian republic Bashkortostan, included 5,891 (80.5%) individuals aged 40+ years out of 7,328 eligible individuals. The participants underwent a detailed interview and medical examination. Arterial hypertension was defined using the criteria defined by the American College of Cardiology/American Heart Association. Results: The prevalence of normal blood pressure (BP), elevated BP, hypertension stage 1, stage 2, and hypertensive crisis was 750/5,891 [12.7%; 95% confidence interval (CI): 4.7, 5.9], 312/5, 891 (5.3%; 95% CI: 4.7, 5.9), 2,187/5,891 (37.1%; 95% CI: 35.9, 38.4), 2,484/5,891 (42.2%; 95% CI: 40.9, 43.4), and 158/5,891 (2.7%; 95% CI: 2.3, 3.1), respectively. The overall prevalence of elevated BP/hypertension was 5,141/5,891 (87.3%; 95% CI: 86.4, 88.1). Awareness of elevated BP/hypertension was 2,289/5,223 (45.4%; 95% CI: 44.0, 47.0). Among 1,055 (20.2%; 95% CI: 19.1, 21.3) individuals under anti-hypertensive treatment, 33 (3.1%) individuals had normal BP values. Higher risk of elevated BP/hypertension was associated with older age [odds ratio (OR): 1.04; 95% CI: 1.03,1.05], male gender (OR: 2.56; 95% CI: 2.10, 3.16), urban region (OR: 1.26; 95% CI: 1.05, 1.51), lower educational level (OR: 0.92; 95% CI: 0.87, 0.97), higher body mass index (OR: 1.15; 95% CI: 1.12, 1.18), higher waist-hip circumference ratio (OR: 6.16; 95% CI: 1.89, 20.0), higher prevalence of sitting or reclining for more than 18 h per week (OR: 1.33; 95% CI: 1.10, 1.61), higher prevalence of alcohol consumption (OR: 1.61; 95% CI: 1.27, 2.05), and higher serum concentrations of triglycerides (OR: 1.22; 95% CI: 1.05, 1.43) and glucose (OR: 1.15; 95% CI: 1.07, 1.24). Using the former definition of hypertension (systolic BP ≥ 140 mmHg and/or diastolic BP ≥ 90 mmHg), the prevalence of hypertension was 3,134/5,891 (53.2%; 95% CI: 51.9, 54.5). Conclusions: Using the new definition of arterial hypertension, the prevalence of elevated BP/hypertension in a typically mixed Russian population aged 40+ years was high (87.3%), with an awareness rate of 45.4% and treatment rate of 20.2%. The rate of therapeutic control of BP elevation in the individuals under treatment was <5%.